Meningkatkan Minat Belajar Bahasa Indonesia dengan Membandingkan Model Pembelajaran RADEC dan Model Pembelajaran Konvensional - Neneng Maryani; Karin Nurseptiani (Latifah Pres, 2019)
This research is based on field findings, namely low interest in learning Indonesian, lack of teacher initiative to use varied learning models that cause students to become bored in following the learning process in Indonesian subjects. The purpose of this study is to find out the increased interest in learning Indonesian by comparing the RADEC (Read, Answer, Discuss, Explain, and Create) learning models and conventional learning. The research method used was Nonequivalent Control Group Design with a population of 173 students, and two sample classes namely class V as an experimental class totaling 28 students and class VI as a control class totaling 37 students. From the results by statistical data using SPSS version 24.0 for windows after the data are declared normally distributed and come from homogeneous samples through normality and homogeneity tests, it is known that the results of hypothesis testing using the Compare Means test with Independent Samples Test obtained sig = 0,000. Because the significance <0.05, it can be concluded that Ho is rejected, which means